2000
DOI: 10.1046/j.1365-2672.2000.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combinations of Fusarium mycotoxins (deoxynivalenol, zearalenone and fumonisin B1) on growth of brewing yeasts

Abstract: The interactive effect of combinations of the Fusarium mycotoxins deoxynivalenol (DON), zearalenone (ZEA) and fumonisin B 1 (FB 1 ) on growth of brewing yeasts was examined. Yeast growth was assessed by measurement of dry weight or relative growth, cell number, viability and conductance change of the growth medium using direct and indirect methods. The interactive effect of a combination of these mycotoxins was subject to the ratio of toxins in the mixture and the toxicity of individual toxins on yeast growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 40 publications
(65 reference statements)
1
30
0
Order By: Relevance
“…Yeast sensitivity to mycotoxins seems to vary with the structural composition of the plasma membrane and the ability of mycotoxins to bind to the cell wall and penetrate the cell (15,20). Mycotoxin effects depend not only on the structure of the cell membrane, which can differ even in the same yeast species, but also on its integrity, which is influenced by a number of factors (5).…”
Section: Yeast Morphology and Growth Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast sensitivity to mycotoxins seems to vary with the structural composition of the plasma membrane and the ability of mycotoxins to bind to the cell wall and penetrate the cell (15,20). Mycotoxin effects depend not only on the structure of the cell membrane, which can differ even in the same yeast species, but also on its integrity, which is influenced by a number of factors (5).…”
Section: Yeast Morphology and Growth Parametersmentioning
confidence: 99%
“…Dziuba et al (5) reported strong inhibition of yeast growth by diacetoxyscirpenol (DAS), a trichothecenes mycotoxin, while ZEA and OTA had a weaker effect. Boeira et al (18)(19)(20) reported significant yeast growth inhibition by the Fusarium toxins, ZEA, DON, and fumonisin B1 (FB1). Similar findings were reported for the trichothecene, T-2 toxin by Foszczyńska and Dziuba (6), and some authors (5,8,17,21,22) have reported that mycotoxins inhibit alcohol dehydrogenase activity and consequently fermentation, lower CO2 release, and affect the production of volatile fermentation by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the pioneering studies on barley which date back to over a century, for example, in the 1900s 53 , in the 1920s 19 , in the 1950s 29,51 , in the 1960s 33 and studies by scientists of the 1970s to the present day 4,6,[12][13][14]18,[20][21][22][23]27,28,[30][31][32][35][36][37][38]40,41,44 , the complexity and incompleteness of our knowledge of grain physiology have resulted in continuous research on cereals, with research studies on barley and malt receiving the most attention when compared to other cereals. This is because of the pivotal role malted barley plays in many applications in the food, alcoholic and non-alcoholic beverage, baked products and the spirit industries.…”
Section: Effect Of Different Steeping Conditions On Endosperm Modificmentioning
confidence: 99%
“…The friabilitimeter was introduced in the early 1980s as a mechanical test to assess the uniformity of endosperm modification of malt samples 24 , although friability scores do not always correlate to brewhouse performance 1,26,27,45,47 . The extensive research into barley has led to a better and in-depth understanding of the physiology of barley and malt 4,6,[12][13][14]18,[20][21][22][23]25,[27][28][29][30]31,32,[35][36][37][38]40,41,44 . As a result, experimental observations and conclusions have been drawn and accepted as a pattern of behaviour for barley and malt.…”
Section: Effect Of Different Steeping Conditions On Endosperm Modificmentioning
confidence: 99%
“…However, investigations on the combined effects of mycotoxins observed in the food supply are scarce. The few studies performed have been based on endpoints that include inhibition of protein and DNA synthesis, DNA methylation and fragmentation, cell viability, and proliferation (15)(16)(17)(18)(19)(20). However, the combined effects of mycotoxins on intestinal immunity are currently poorly understood.…”
mentioning
confidence: 99%